Systematic evaluation of non-animal test methods for skin sensitisation safety assessment. Issue 1 (February 2015) - Reisinger, Kerstin; Hoffmann, Sebastian; Alépée, Nathalie; Ashikaga, Takao; Barroso, Joao; Elcombe, Cliff; Gellatly, Nicola; Galbiati, Valentina; Gibbs, Susan; Groux, Hervé; Hibatallah, Jalila; Keller, Donald; et al.
Highlights Non-animal data for skin sensitisation risk assessment are urgently needed. This has led to the development of a number of in vitro test methods. Cosmetics Europe (CE) systematically evaluated 16 of these methods. Methods were prioritised for further in-depth evaluation. CE will develop a testing strategy for skin sensitiser potency prediction.